Preoperative factors associated with hypotension in young anaesthetised dogs undergoing elective desexing. Issue 4 (April 2015) - Costa, RS; Raisis, AL; Hosgood, G; Musk, GC
Abstract : Objectives: Document the proportion of dogs with perioperative hypotension and explore the association of sex, age and body mass and indices of hydration with mean arterial blood pressure (MAP) in two cohorts of young, healthy anaesthetised dogs. Methods: Dogs were anaesthetised with a standardised protocol. The proportion of dogs with invasively measured MAP <60 mmHg for ≥10 min was recorded. The area under the MAP*time curve (MAP‐AUC) was calculated for a standard perioperative period. The association of explanatory variables, including sex, age, body mass and indices of hydration (urine specific gravity (USG), packed cell volume and total solids) measured prior to surgery, with the MAP‐AUC was explored using regression analysis in the first cohort (n = 71) and externally validated in the second cohort (n = 24). Results: In cohort 1, 35 of 71 dogs (0.49, 95% confidence interval (CI) 0.37–0.61) dogs and 17/24 dogs in cohort 2 (0.71, 95% CI 0.53–0.89) developed hypotension. Regression analysis showed that age and USG were significantly associated with MAP‐AUC for cohort 1 (P = 0.0138). There was a positive association of MAP‐AUC with age and a negative association with USG. The association of MAP‐AUC with USG was supported in cohort 2, with a significant negative association (P = 0.014, r = −0.54) Conclusion: The high frequency of hypotension in both cohorts supports blood pressure monitoring during anaesthesia of young, healthy dogs. USG, an index of hydration, appears negatively associated with MAP during anaesthesia, suggesting that subclinical dehydration may contribute to lower MAP during surgical anaesthesia.